Save Guiding of Visually Impaired People - Artificial Guiding Lines Arrangements in the Infrastructure - Košťálová, Jana; Matuška, Jaroslav (City Net Scientific Research Center, 2016)
The paper presents arrangements that ensure safe mobility of visually impaired people in public places and sites intended for transport. An analysis of the current situation points to the fact that there is a real problem in using artificial guiding lines as for their parameter differentiation in interior and exterior. Some countries do not use artificial guiding lines at all while others overuse them; moreover, they use different parameters and surface. The article shows how logic is applied in the creation of barrier free environment, where artificial guiding lines are an integral part. Further, the article defines fundamental features and parameters of the artificial guiding lines in the Czech Republic. The aim of the paper is to propose a gradual convergence of tactile arrangement systems, especially for the guiding lines, which are one of the most fundamental requirements for safe mobility of visually impaired people.
Bezpečné vedení osob s postižením zraku - úpravy umělých vodicích linií
Keywords: accessibility; barrier free environment; Design for All; guiding lines; safety; visually impaired people; bezbariérové prostředí; bezpečnost; design for All; přístupnost; vodicí linie; zrakové postižení